EFFECTIVE METHODS OF LEARNING ENGLISH IN THE MODERN WORLD - Ulugbek Yarashovich Elmurodov (Bright Mind Publishing, 2025)
This article explores modern approaches to learning English that enable learners to achieve a high level of language proficiency in the shortest possible time. Special attention is paid to the use of technology, communicative methods, and self-directed learning. The results of a study conducted among students learning English are presented, along with recommendations for optimizing the learning process. The article will be useful for both teachers and students looking to improve their language skills.
Keywords: English learning, modern methods, communicative approach, technology in education, gamification, self-directed learning, language acquisition, student motivation, online platforms, language proficiency.